High-Performance Two-Stage DC/DC Converter Based on LADRC-PI Hybrid Control for PEM Electrolyzer Hydrogen Production - Qingshuai Yu; Zhenao Sun; Yetong Han; Tuanlong Zhang; Rongxing Zhang; Muhua Lin (Micromachines)
While DC/DC converters for water electrolysis systems have been widely investigated, they inherently face a critical compromise between wide voltage regulation capabilities and dynamic response characteristics. This study is based on a two-stage hybrid topology (TSIB-TPLLC) that synergistically combines a two-phase interleaved buck converter with a three-phase LLC resonant converter to resolve this challenge. The first-stage interleaved buck converter enables wide-range voltage regulation while reducing input current ripple and minimizing intermediate bus capacitance through phase-interleaved operation. The subsequent three-phase LLC stage operates at a fixed resonant frequency, achieving inherent output current ripple suppression through multi-phase cancellation while maintaining high conversion efficiency. A dual-loop control architecture incorporating linear active disturbance rejection control (LADRC) with PI compensation is developed to improve transient response compared to conventional PI-based methods. Finally, a 1.2 kW experimental prototype with an input voltage of 250 V and an output voltage of 24 V demonstrates the converter’s operational feasibility and enhanced steady-state/transient performance, confirming its suitability for hydrogen production applications.